The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/0735648x.2019.1692420
|View full text |Cite
|
Sign up to set email alerts
|

Money talksmoney laundering choices of organized crime offenders in a digital age

Abstract: In this explorative study we provide empirical insight into how organized crime offenders use IT to launder their money. Our empirical data consist of 30 large-scale criminal investigations into organized crime. These cases are part of the most recent, fifth data sweep of the Dutch Organized Crime Monitor (DOCM). We do not focus on cybercrime alone. Instead, we explore the financial aspects of criminal operations in a broad range of types of organized crime, i.e. from 'traditional' types of organized crime, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…All criminals now have the option of utilizing cyberspaces through the dark web or encrypted apps to communicate anonymously (Kassab & Rosen, 2019;Saito, 2021). There have been several studies that have shown that the use of the internet has created more efficient measures in trafficking illicit substances and products, which only contribute to The Journal of Intelligence, Conflict, and Warfare the expansion of business opportunities for organized crime groups (Kruisbergen et al, 2019). For example, potential buyers/consumers have increased largely because of the global reach technology has created for all users and distributors (Kassab & Rosen, 2019).…”
Section: Transnational Organized Crime: Technological Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…All criminals now have the option of utilizing cyberspaces through the dark web or encrypted apps to communicate anonymously (Kassab & Rosen, 2019;Saito, 2021). There have been several studies that have shown that the use of the internet has created more efficient measures in trafficking illicit substances and products, which only contribute to The Journal of Intelligence, Conflict, and Warfare the expansion of business opportunities for organized crime groups (Kruisbergen et al, 2019). For example, potential buyers/consumers have increased largely because of the global reach technology has created for all users and distributors (Kassab & Rosen, 2019).…”
Section: Transnational Organized Crime: Technological Benefitsmentioning
confidence: 99%
“…The word 'transnational' refers to the ability to go beyond borders, boundaries, jurisdictions, and nations. Technology has extended boundaries and reach for several businesses, including organized crime entities (Kassab & Rosen, 2019;Kruisbergen et al, 2019;Saito, 2021). Transnational organized crime operates globally with various markets in different countries (Kassab & Rosen, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…European lawyers and notaries would normally ask for the source of funds, and be expected to check on what they are told, though they may not all investigate with equal diligence or forensic skill. regard to concealment, but also has its own detours to convert into the ownership of our hypothetical house (Kruisbergen et al 2019). Fraud offenses, on the other hand, normally generate proceeds of crime that are already in the financial system and are thus more easily moved around to finance a purchase, e.g.…”
Section: Type Of Crimementioning
confidence: 99%
“…The ability to exchange information quickly with foreign partners without any unreasonable obstacles or delays is becoming a staple of any FIU, law enforcements or public agencies (Hutley- . Currently, anti-money laundering is becoming an issue of countries around the world and starting the cooperation process in the prevention of money laundering, especially through the financial-banking system to prevent criminal organizations from turning nations into places that wash away crime-related properties and money due to their size and harm to the national economy (Kruisbergen, Leukfeldt, Kleemans, & Roks, 2019). Indeep, the anti-money laundering laws of the countries, the most mentioned issues about international cooperation focus on some key points of either bilateral or multilateral judicial assistance as well as recognition of foreign judgments (Hutley- Kruisbergen et al, 2019).…”
Section: International Cooperation Against Money Laundering: An Overall Contextmentioning
confidence: 99%